2022
DOI: 10.1039/d1sm01706c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of ethyl cellulose particles with different morphologies through microfluidics

Abstract: In this paper, a microfluidic method is proposed for fabricating ethyl cellulose particles with different morphologies through extraction and solidification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…31 Cui et al fabricated ethyl cellulose particles with different morphologies, including red-bloodcell-like, doughnut-like, dimpled, and spherical particles by changing the operating parameters in a homemade microfluidic system. 32 Apparently, these studies indicate that microfluidics exhibit superior properties in terms of the crystal morphology design and particle size control. Furthermore, microfluidics offers many other advantages, such as simplified equipment and flexible regulation; it facilitates screening and production at low throughput, especially for high-value pharmaceuticals, and there is ease of technology transfer and scale-up.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…31 Cui et al fabricated ethyl cellulose particles with different morphologies, including red-bloodcell-like, doughnut-like, dimpled, and spherical particles by changing the operating parameters in a homemade microfluidic system. 32 Apparently, these studies indicate that microfluidics exhibit superior properties in terms of the crystal morphology design and particle size control. Furthermore, microfluidics offers many other advantages, such as simplified equipment and flexible regulation; it facilitates screening and production at low throughput, especially for high-value pharmaceuticals, and there is ease of technology transfer and scale-up.…”
Section: Introductionmentioning
confidence: 91%
“…Compared with commercial products, the crystal size distribution is more uniform, reducing by 60% . Cui et al fabricated ethyl cellulose particles with different morphologies, including red-blood-cell-like, doughnut-like, dimpled, and spherical particles by changing the operating parameters in a homemade microfluidic system . Apparently, these studies indicate that microfluidics exhibit superior properties in terms of the crystal morphology design and particle size control.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and co‐workers fabricated red‐blood‐cell‐like ethyl cellulose microparticles through extraction and solidification in a double T‐junction microfluidic device. [ 117 ] By adjusting the flow rates and ethyl cellulose concentration, they obtained monodisperse particles with bioinspired shapes, and determined the regime of particle morphology. Tsai and co‐workers developed a microfluidic‐based approach for creating spiky microparticles through ionic crosslinking in an aqueous two‐phase system (Figure 9B).…”
Section: Polymeric Microparticles Fabricated By Droplet‐based Microfl...mentioning
confidence: 99%
“…Natural materials, such as cellulose, chitosan, and lignin, have been extensively investigated as environmentally friendly fillers for polymer composites. Cellulose, as the most abundant sustainable polymer, is particularly attractive considering its low cost, wide availability, and high strength property. Ethyl cellulose (EC) is one kind of cellulose derivative in which the hydroxyl groups on the repeating glucose unit are replaced by ether groups. , EC is hydrophobic and lipophilic, which is stable in aqueous, acidic, and alkali solutions . For instance, Lu et al fabricated an ethyl cellulose sponge and found that the sponge exhibited robust superhydrophobicity and excellent recyclability .…”
Section: Introductionmentioning
confidence: 99%
“…16−18 Ethyl cellulose (EC) is one kind of cellulose derivative in which the hydroxyl groups on the repeating glucose unit are replaced by ether groups. 19,20 EC is hydrophobic and lipophilic, which is stable in aqueous, acidic, and alkali solutions. 21 For instance, Lu et al fabricated an ethyl cellulose sponge and found that the sponge exhibited robust superhydrophobicity and excellent recyclability.…”
Section: Introductionmentioning
confidence: 99%